Innovation and Scaling Research Partner Search: Preliminary Report - Tierney, Nikki (CGIAR, 2023)
This report covers a subset of activity to provide breadth and objectivity to the provider inventory. The intention is to cast a wide net, and assess potential providers against objective criteria.